PERANCANGAN SISTEM INFORMASI DETAK JANTUNG BERBASIS ANDROID PHONE MENGGUNAKAN MEDIA BLUETOOTH - Yussa Ananda (Jurnal Simetri Rekayasa, 2021)
The heart is one of the important organs owned by humans which functions to pump blood throughout the body and accommodate it after being cleaned by the lungs. Heart rate in beats per minute (bpm) is a parameter that shows the condition of the heart, and the way to know the condition of the heart is to know the frequency of the heartbeat. A wireless heart rate monitoring system has been designed using bluetooth and smartphone technology. This will make it easier for doctors and nurses to monitor the patient's heart condition in real time. An infrared sensor is attached to the patient's finger to pick up heart rate signals through the bloodstream. This signal is converted into logic and then read by an Atmega 8 controller. The controller will calibrate pulses against time so that data on the number of beats per minute is obtained. The calibration results are then sent by the controller to the smartphone via the HC-05 bluetooth adapter. The data received by the smartphone is then displayed through an application, namely bluetooth electronics. The system has been successfully tested on several volunteers with different data according to the conditions of the volunteers. The test results are quite accurate with a margin of error not exceeding 5%